PEMBELAJARAN MULTIKULTURAL PADA MATERI KEBERAGAMAN BUDAYA DAN KEARIFAN LOKAL DALAM MENINGKATKAN SIKAP TOLERANSI SISWA - Rahmadewi, Anzani; Zakiyah, Hana; Nurkamila, Risma; Wahyuningsih, Yona (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the challenges of a multicultural society, especially in Indonesia, which is full of diversity in terms of ethnicity, race, language,religion, socio-economics, and many other aspects. However, the richness of this diversity often gives rise to intolerance in society. Therefore, the education system is capable of ending perceptions of differences between ethnicities, races, ethnicities, languages,religions, socioeconomic status, and other diversities. By fostering this through education, it can be expected to provide a deep understanding of the attitude of tolerance that must be built in a country full of diversity. The research method used by the author is a Systematic LiteratureReview obtained from reference data, journals, and all reference sources. Teaching multicultural values in elementary school is very important in shaping students' personalities to be tolerant and respectful of differences.In elementary education, Social Studies is a subject that is very relevant for applying a multicultural approach. This is because IPS directly discusses various aspects of social, cultural, and economic life, as well as how people interact in a diverse society. Thus, multicultural learning can be an appropriate strategy for improving students' attitudes of tolerance by integrating material on cultural diversity and local wisdom to relate attitudes of tolerance to the differences that occur.